IMPLEMENTASI METODE PROTOTYPING PADA SISTEM INFORMASI PENGADAAN BARANG CETAKAN BERBASIS WEB - Dony Ardiyansah; Omar Pahlevi; Tri Santoso (Hexagon Jurnal Teknik dan Sains, 2021)
A fast and accurate data processing information system is needed by various parties in the business world, especially in the banking sector, procurement information systems are generally very necessary to accelerate the completion of administrative work on the part of the procurement unit. PT. Bank ICBC Indonesia is a dynamic and modern banking system, almost all work is supported by a computerized system, but there are certain parts in the process that are still manual, an obstacle that is often found here is the lack of control over the process of recording the receipt and release of goods so that between the available data and In-stock items do not match. Documentation problems that are still done manually and the lack of control over the process of recording the receipt and release of goods so that the data available with the stock of goods can be inappropriate. Therefore it is necessary to have a printed procurement information system that is able to minimize input errors while providing a more efficient and accurate report. This research uses the prototype method as an application development method with the PHP programming language, MySQL database and Adobe Dreamweaver CS5 so as to produce a web-based application that can be used by the work unit for the procurement of goods and services.